The IMPLEMENTATION OF STORY CHAIN ACTIVITIES TO ENHANCE YOUNG LEARNERS’ SPEAKING PERFORMANCE AND CREATIVITY - Nurul Meilinasari; Sulistyani; Khoiriyah (Universitas PGRI Ronggolawe Tuban, 2025)
This study investigates the implementation of Story Chain activities focusing to see its potential in enhancing students’ speaking performance and creativity of young learners in English as a Foreign Language (EFL) contexts. Utilizing a qualitative research approach, the data were collected through interviews and direct observations. The findings reveal that Story Chain activities significantly improve students' speaking proficiency, creativity, and confidence. Students demonstrated enhanced vocabulary usage, pronunciation, and the ability to construct coherent narratives. Additionally, the collaborative nature of the activities fostered social interaction and an inclusive classroom environment. However, challenges were identified, including difficulties faced by students with lower English proficiency and those who were initially reluctant to participate. Despite these challenges, the research underscores the effectiveness of Story Chain activities in creating an engaging and supportive learning environment. Suggestions for teachers and future researchers are to optimize the application of this method in diverse educational settings.